Inclusion of persons with disability in sport: part 1 – rights and challenges in Qatar - Sanaa Taha Al-Harahsheh (18279013) (2022)
Sport is considered a powerful tool to foster social inclusion and improve the well-being of persons with disabilities (PWDs). While it can place people on equitable social footing,1 PWDs remain under-represented in sport and physical activities compared with their peers without disabilities. The participation of PWDs in sport is influenced by the type and severity of disability. Those with learning disabilities or with profound and multiple disabilities have the lowest participation levels.1 Globally, disability rates are rising dramatically, presently estimated at over 1 billion people—including 190 million people (3.8%) who experience significant difficulties in functioning.2 In Qatar, census data estimates 1.2% of the population have a disability, with 232 athletes registered at the Qatar Paralympic Committee (QPC).3 However, it is important to note that defining and operationalising disability remains a challenge despite significant progress in measurement. Qatar has around 1.3 million employees, mostly young, healthy men, and uses a narrow definition of disability when estimating the number of PWDs. Therefore, the Washington Group Questions should be adopted in the future to measure PWDs more accurately.4 Over the past few decades, the State of Qatar has achieved tangible progress in catering to the needs of PWDs. For example, various projects, initiative and programmes that accommodate to the needs of PWDs, while protecting their basic human rights were developed. Furthermore, the QPC is not only committed to enabling para-athletes to achieve sporting excellence but also to developing sport opportunities for all PWDs in Qatar (beginner to elite).5 This editorial reflects on how sport and physical activities affect PWDs in Qatar and the obstacles to their participation. Other Information Published in: British Journal of Sports Medicine License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1136/bjsports-2022-106224